Framing of TikTok Social Media in the 2024 Indonesian Presidential Election Campaign - Fadilla Syahriani; Navisa Latifa Auliya; Nadyya Zahratul Jannah (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
This study aims to examine the role of TikTok in the framing of political campaigns during the 2024 Indonesian Presidential Election. The research focuses on how TikTok, as a dominant social media platform, influences public perception and political communication. Using a qualitative content analysis method, this study analyzes selected TikTok videos from prominent political candidates and their supporters, focusing on the themes, narratives, and visuals used in their campaigns. The findings reveal that TikTok is increasingly utilized to create emotional engagement, targeting younger voters through viral content and interactive features. Candidates use TikTok to present a more personal and relatable image, while also engaging with political issues through memes, short clips, and hashtag campaigns. The research concludes that TikTok plays a significant role in shaping electoral discourse by allowing real-time, creative, and participatory interactions between candidates and voters. This study contributes to the academic understanding of digital political communication, highlighting TikTok's potential as a powerful tool for political engagement and its impact on voter behavior, particularly among younger demographics. It also underscores the evolving nature of media consumption and its implications for the political landscape in Indonesia. The findings offer insights for future studies on social media's influence in electoral campaigns, particularly in emerging democracies where digital platforms are gaining prominence.